Pengaruh Pemberian Insentif Dan Motivasi Kerja Terhadap Kinerja Karyawan PT Perkebunan Nusantara V Kebun Sei Galuh Kecamatan Tapung, Riau - Gultom , Dona Esra Mariana; Sihombing , Natalia ET Sihombing; Sinaga, Kepler Sinaga (Jurnal Ilmu Sosial Dan Politik, 2023)
The purpose of this study was to determine the effect of providing incentives and work motivation on the performance of employees of PT Perkebunan Nusantara V Kebun Sei Galuh Tapung District, Riau. The method used is associative quantitative method and data collection techniques using a questionnaire with a sample of 74 respondents. The data analysis method used is the instrument test, classical assumption test and hypothesis testing with help through the SPSS 25 application.The results showed that the provision of incentives and work motivation had a significant effect on the performance of employees of PT Perkebunan Nusantara V Kebun Sei Galuh Tapung District, Riau. This is indicated by the t value of the incentive variable (X1) is greater than the t table value (6.265> 1.993) with a significant level of 0.00 <0.05. The t value of the motivation variable (X2) is greater than the t table value (5.957> 1.993) with a significant level of 0.00 < 0.05. Simultaneously, the calculated F value is greater than the F table (64.947> 3.12) with a significant level of 0.00 <0.05. The coefficient of determination is obtained at 0.647, which means that the incentive and motivation variables can explain the employee performance variable by 64.7%, while the remaining 35.3% is influenced by other variables outside of this research variable.